Determinants of Genetic Structure in a Highly Heterogeneous Landscape in Southwest China - Wambulwa, Moses C.; Luo, Ya-Huang; Zhu, Guang-Fu; Milne, Richard; Wachira, Francis N.; Wu, Zeng-Yuan; Wang, Hong; Gao, Lian-Ming; Li, De-Zhu; Liu, Jie (Frontiers in Plant Science, 2022)
Intra-specific genetic diversity is a fundamental component of biodiversity, and is key to species adaptation and persistence. However, significant knowledge gaps still exist in our understanding of the patterns of genetic diversity and their key determinants. Most previous investigations mainly utilized single-species and/or a limited number of explanatory variables, so here we mapped the patterns of genetic diversity within 15 plant species, and explored the key determinants shaping these patterns using a wide range of variables. Population-level cpDNA sequence data for 15 plant species from the Longitudinal Range Gorge Region (LRGR), southwest China, were retrieved from literature, and used to estimate haplotype diversity (HD) and population pairwise genetic differentiation (FST) indices. Genetic diversity and divergence landscape surfaces were then generated based on the HD and FST respectively, to clarify the patterns of genetic structure in the region. Subsequently, we analyzed the relationships between genetic diversity and 16 explanatory variables (classified as anthropogenic, climatic, and topographic). We found that the highest genetic diversity occurred in the Yulong Mountain, with a significant proportion (~74.81%) of the high diversity land area being located outside of protected areas. The highest genetic divergence was observed approximately along the 25°N latitudinal line, with notable peaks in the western and eastern edges of the LRGR. Genetic diversity (HD) was weakly but significantly positively correlated with both Latitude (lat) and Annual Mean Wet Day Frequency (wet), yet significantly negatively correlated with all of Longitude (long), Annual Mean Cloud Cover Percent (cld), Annual Mean Anthropogenic Flux (ahf), and Human Footprint Index (hfp). A combination of climatic, topographic and anthropogenic factors explained a significant proportion (78%) of genetic variation, with topographic factors (lat and long) being the best predictors. Our analysis identified areas of high genetic diversity (genetic diversity ‘hotspots’) and divergence in the region, and these should be prioritized for conservation. This study contributes to a better understanding of the features that shape the distribution of genetic diversity in the LRGR, and thus would inform conservation management efforts in this species-rich, but vulnerable region.